Religious Dialogue on Social Media: The Khilafah Issue Between Pluralist and Scripturalist Muslims - Muhammad Kasim (Asyahid Journal of Islamic and Quranic Studies (AJIQS), 2022)
Great efforts have been exhausted to bring religion closer to the media (as opposed to bringing media closer to religion), or to break down the traditional boundaries between "religion" and "media". In light of these efforts and various studies, some have tried to point out the need to build new bridges between religion and the media. This effort has even led scholars to believe that in the "age of media", the secular is holy and the holy is secular. This effort is aimed at unifying the two important elements of contemporary human life, which historically can also be understood in the context of challenging the relationship between science and religion. In this paper, we classify various theories and approaches regarding the essence of media into three branches: functionalistic, essentialist, and hypothetical interactive. After a brief review of the ramifications of each theory's compatibility or incompatibility with media, religion, and religious teachings, it is shown that more fundamental steps must be taken to unify religion and media in the era known as "Global", "Religion", or "The Age of Religion". Media". Another section of this paper is devoted to the necessary distinction between media religion and mediated religion, emphasizing the main characteristics of religious media theory. Although the basic tenets of media essentialism have been accepted, religion, which is neither institutional ministry nor absolute personal experience, has the potential to be consistent with the exclusive nature of its media. The last section of this article points to the religious focus axis of the media hypothesis in which the elements of religion, culture, globalization, and media are balanced and stable. This is religious pluralism. Keywords: Religion, Interactive Dialogue Abstrak Upaya-upaya besar telah habis untuk mendekatkan agama ke media (sebaliknya daripada mendekatkan media dengan agama), atau mendobrak batas-batas tradisional antara "agama" dan "media". Mengingat upaya tersebut dan berbagai penelitian, beberapa telah mencoba untuk menunjukkan perlunya membangun jembatan baru antara agama dan media. Upaya ini bahkan membuat para sarjana percaya bahwa di "era media", sekuler itu suci dan yang suci itu sekuler. Upaya ini ditujukan untuk penyatuan dari dua elemen penting kehidupan manusia kontemporer, yang secara historis dapat juga dipahami dalam konteks menantang hubungan antara sains dan agama. Dalam tulisan ini, dilakukan klasifikasi berbagai teori dan pendekatan tentang esensi media dalam tiga cabang: fungsionalistik, esensialis, dan interaktif hipotesis. Setelah tinjauan singkat tentang konsekuensi dari kompatibilitas masing-masing teori atau ketidaksesuaian dengan media, agama, dan ajaran agama, ditunjukkan bahwa lebih langkah mendasar harus diambil untuk menggabungkan agama dan media di era yang dikenal sebagai ”Global”, ”Agama”, atau ”Zaman Media”. Bagian lain dari karya tulis ini dikhususkan untuk perbedaan yang diperlukan antara media agama dan agama yang dimediasi, menekankan karakteristik utama teori media religi. Meskipun prinsip dasar media esensialisme telah diterima, agama, yang bukan kementerian institusional maupun pengalaman pribadi yang mutlak, memiliki potensi untuk konsisten dengan eksklusif sifat medianya. Bagian terakhir dari artikel ini menunjuk ke poros fokus agama hipotesis media di mana unsur-unsur agama, budaya, globalisasi, dan media seimbang dan stabil. Inilah pluralisme agama. Kata Kunci: Agama, Dialog Interaktif